Audit Energi Dengan Pendekatan Metode Ahp (Analythical Hierarchy Process) Untuk Penghematan Energi Listrik (Studi Kasus: PT.Solo Grafika Utama) - Werdaningsih, Yanuarti, Ratnanto Fitriadi, ST,MT (2016)
Increased development that followed the economic development of Indonesia resulted in the national energy demand is increasing. One of the energy in Indonesia continues to increase is electrical energy. The electric energy is supplied from power plants, including steam (coal-fired) power and gas (fuel gas). Coal and natural gas is one source of energy that can not replaces. Therefore, its use should be as good as possible for sustainable energy reserves for future generations. PT ABC is a company engaged in the printing that provide printing services one Solopos newspapers and some school books and magazines. However, the company has been no activity for energy management data to improve using efficient energy. Energy auditing is a technique used to calculate the amount of energy consumption in a building / buildings and identify ways for savings. AHP (Analytical Hierarchy Process) is a decision making method that describes the problem multi-factor or a complex multi-criteria into a hierarchy. Newspaper production average was in the amount of 500-600 thousand circulation within a period of one year and the average non newspapers are in the amount of 600 thousand circulation. Electricity costs incurred on average in a month is Rp 30,815,544. Based on AHP processing sequence based on weight-saving alternative is austerity measures on today's technology with a weighting of 53.1%, energy saving measures on employees 29.9%, Use of New Technology 16.9% energy saving. Keywords: AHP, Saving Alternative, Energy Audit, Energy Efficiency Power